PEIRCE COLLEGE AND STUDENT SUCCESS - Lenrow, Jon (Online Learning, 2009)
This case study describes the philosophy underlying the delivery of online programs and courses at Peirce College through Peirce Online. The strategies used to implement the Peirce College model and the measures used to validate its success are outlined. These factors are reviewed in the context of the Sloan-C Five Pillars for quality learning environments.